Identifying psychological and socio-cultural characteristics of the coloured policyholder market segment in the Western Cape : a psychographic profile analysis in the life assurance industry - Bruce, Ferdinand C.(Ferdinand Christoffel) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Econ.) -- University of Stellenbosch, 1988.